Neutrophil Gelatinase-Associated Lipocalin (NGAL) in Urine as a Potential Non-Invasive Method for Determine Kidney Damage in Predialysis Patients - Titisari, Nurina; Hernowati, Tinny Endang; Ratnawati, Retty; Fauzi, Ahmad; Gunawan, Atma; Jaya, Wiwi (Research Journal of Life Science, 2021)
NGAL expression in acute kidney failure is well known. It is approved that NGAL expression occurs earlier than the level of BUN and creatinine in acute kidney failure. NGAL is not only expressed in the blood but also in the urine, where urine collection has many advantages over blood collection. This study aims to observed the expression of NGAL in predialysis patients and to determine the correlation between NGAL serum and NGAL urine of patients. The sample was taken from healthy persons as control and predialysis patients. The examination of BUN, creatinine, and urinalysis were done to approve the diagnose in predialysis patients. While NGAL in serum and urine were analyzed using the Enzyme-Linked Immunoabsorbent Assay (ELISA). The results showed that the concentration of NGAL in serum was higher in the predialysis patients compared to the healthy subjects (p<0.05). There was a strong positive correlation between the NGAL in the serum and the NGAL in the urine (r= 0.98 and p<0.000). It is concluded that the non-invasive examination of NGAL in urine can be choose rather than using serum NGAL. However, it must be noted that NGAL could be used for chronic renal failure in predialysis patients as long as other biomarkers have been proven.